KINERJA KEUANGAN PERUSAHAAN DAERAH AIR MINUM KOTA SAMARINDA - Titin Ruliana; Eddy Soegiarto K (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2015)
Regional Water Company (It’s call PDAM) running the company well, especially the increase in the company's performance. PDAM performance as the Regional Owned Enterprises (enterprises) influenced by PDAM ability to pay debts of the company. It is known that the debts PDAM Samarinda enough to affect the revenues and costs, water treatment that requires no small cost that makes spending much of the income (profit) derived from the sale of water of PDAM Samarinda city. Improvements continue dilalukan so that the performance of PDAM Samarinda city increased through the classification level of success PDAM. The purpose of this study was to analyze the development of financial performance PDAM of Samarinda city based Kepmendagri No. 47 of 1999 from the year 2011 up to 2012. Based on the assessment of performance has been analyzed, that the value obtained for the year 2011 and the year 2012 is 35 with a weighting of 27.25%. Judging from the values obtained and the weight is known that the performance of financial performance PDAM Samarinda is well in the year 2011 to the year 2012, but otherwise has not reached its maximum value and performance weight based Kepmendagri No. 47 of 1999 which is the value of 60